Semi-jaringan polimer saling menusuk (Semi-IPN) berasaskan getah asli melalui teknik sinaran - Hirzin, Radin Siti Fazlina Nazrah (2004)
Electron beam irradiation of acrylated liquid natural rubber (ALNR)/natural rubber (NR) blends to form semi-interpenetrating polymer networks (semi-LPNs) was the subject of study in this work. Initially, NR was subjected to dtra violet (UV) radiation for about forty hours to produce a low molecular weight liquid natural rubber (LNR). The process was followed by treatment of the LNR with a reducing agent to produce hydroxylated liquid natural rubber (HLNR) which was then converted to ALNR by an acrylation process. The molecular weights of LNR, HLNR and ALNR were determined using gel permeation chromatography (GPC). Structural characterization of the HLNR, ALNR and the semi-IPN were investigated by fourier transform infrared (FT-IR) and nuclear magnetic resonance (NMR) spectroscopies. Differential scanning calorimetry (DSC), thermogravimetry analyzer (TGA) and universal testing machine were used to study the physical and mechanical properties of the semi-IPNs. The effects of multifunctional acrylates (MFA), TPGDA and TMPTA on the properties of semi-IPNs were also studied. From the results obtained it was found that the TMPTA gave higher crosslink density and gel fraction of the semi-IPNs as compared to TPGDA. Enhancement in the mechanical properties was achieved with the increase of radiation dose. It was evident from the DSC results that the semi-IPNs produced exhibited glass transition temperatures (T,). In addition, the TGA characterization showed that the semi-IPNs have a good thermal stability when they were exposed to 200 kGy of radiation dose. The morphology of semi-IFWs, which were studied by scanning electron microscopy (SEM), indicated the compatibility of semi-IPN obtained at 200 kGy radiation dose.